Report on Indonesia Mining Sector Diagnostic - Indonesian Mining Institute (World Bank, Washington, DC, 2019)
The Mining sector diagnostic (MSD) is a tool the World Bank has developed to: (1) comprehensively assess the laws, policies, and regulations in a country's mining sector; and (2) identify the strengths and weaknesses of the institutions that administer` the laws, policies, and regulations and monitor and regulate the sector. The Indonesia MSD collects and shares information on the nation's mining sector's management structure and governance. It analyzes the rules and policies that exist in the mining sector and the gap between those rules and their implementation in practice. For the government to optimize the management of and benefits stream from its mining industry, it agrees to receive support from the World Bank to undertake policy analysis and design reforms through the Natural Resources for Development (NR4D) program. This report is organized as follows: an introduction, followed by chapter 2, which provides an overview of the mining sector in Indonesia, its importance in the overall economy, the main institutional roles and responsibilities, and the legal and regulatory framework governing the sector. Chapter 3 presents a high-level summary of the results of the MSD, discussing the data as aggregated into the MSD dashboard and analyzing implementation gaps between de jure and de facto performance. Chapter 4 discusses the detailed findings regarding the strengths and weaknesses of Indonesia's mining sector. The MSD also assesses the context and enabling environment of the mining sector, the results of which are presented in chapter 5. Chapter 6 analyzes stakeholder priorities defined as those areas that respondents identified as key priority areas, reforms in which would have a significant impact on improving the contribution of the mining sector to sustainable economic development and the well-being of the entire population. Chapter 7 concludes with a summary of sector strengths.